NSD2 Promotes Renal Cancer Progression Through Stimulating Akt/Erk Signaling - Han, Xu (Cancer Manag Res, 2020)
BACKGROUND: Nuclear receptor suppressor of variegation, enhancer of zeste, and trithorax (SET) domain-containing 2 (NSD2), is a well-known histone lysine methyltransferase (HMTase). The aim of this study was to investigate the biological role of NSD2 in clear cell renal cell carcinoma (ccRCC). METHODS: GEO and OncoLnc databases were used to identify NSD2 expression and estimate its clinical value in ccRCC. Immunohistochemistry (IHC) was applied to further evaluate NSD2 protein level in ccRCC tissues. The expression of NSD2 in different cell lines and the transfection efficiency were determined by quantitative real-time PCR and Western blot analysis. The effect of NSD2 and the underlying mechanism in ccRCC progression were investigated via MTT, flow cytometry, Western blotting and xenograft tumor assays. RESULTS: NSD2 was over-expressed in both ccRCC tissues and cell lines. NSD2 expression could discriminate ccRCC samples from normal samples, and moreover, high NSD2 expression was characterized with a short overall survival (OS) time. Additionally, knockdown of NSD2 suppressed proliferation and induced apoptosis of cancer cells by inhibiting Akt/Erk signaling and regulating Bcl-2 and Bax expression. Meanwhile, up-regulation of NSD2 contributed to the opposite effects. Silencing of NSD2 reduced xenograft tumor growth in vivo. CONCLUSION: NSD2 serves as an oncogenic factor in the progression of ccRCC via activation of Akt/Erk signaling.